Optimizing maxillary aesthetics of a severe compromised tooth through orthodontic movement and dental implants - Molon, Rafael Scaf [UNESP]; Avila, Erica Dorigatti de [UNESP]; Cirelli, Joni Augusto; Cardoso, Mauricio de Almeida; Capelloza Filho, Leopoldino; Barros, Luiz Antônio Borelli [UNESP] (Hindawi, 2014)
Treatment of severe compromised tooth in the maxillary anterior area still poses great challenge to the clinicians. Several treatment modalities have been proposed to restore the function and aesthetics in teeth with advanced periodontal disease. The present study aims to report a case of traumatic injury of a left-maxillary central incisor with ridge preservation, orthodontic movement, and implant therapy. A 45-year-old woman underwent the proposed treatment for her left central incisor: basic periodontal therapy, xenogenous bone graft, and guided bone regeneration (GBR). Six months after the graft procedure, orthodontic movement by means of alignment and leveling was made and a coronal displacement of the gingival margin and vertical bone apposition could be observed after 13 months of active movement. Afterwards, a dental implant was placed followed by a connective tissue graft and immediate provisionalization of the crown. In conclusion, orthodontic movement was effective to improve the gingival tissue and alveolar bone prior to implant placement favoring the aesthetic results. Six years postoperatively, the results revealed height and width alveolar bone gain indicating that the treatment proposed was able to restore all the functional and aesthetic parameters.